Monocyte-dependent co-stimulation of cytokine induction in human γδ T cells by TLR8 RNA ligands - Ruben Serrano (Nature Portfolio, 2021)
Abstract Human Vγ9Vδ2 T cells recognize pyrophosphates produced by microbes and transformed cells and play a role in anti-infective immunity and tumor surveillance. Toll-like receptors (TLR) are pattern recognition receptors in innate immune cells which sense microbial structures including nucleic acids. Given that γδ T cells are in clinical development for application in cellular cancer immunotherapy and TLR ligands have potent adjuvant activity, we investigated the co-stimulatory role of selected TLR ligands in γδ T-cell activation. Here we have used recently described RNA ligands for TLR7 and TLR8 together with Vγ9Vδ2 T-cell specific pyrophosphate antigens to analyze the rapid cytokine induction in Vδ2 T cells as well as the accessory cell requirements. While TLR8- as well as TLR7/8-specific RNA did not induce IFN-γ in Vδ2 T cells on their own, they provided strong co-stimulation for Vδ2 T cells within peripheral blood mononuclear cells in the presence of additional T-cell receptor activation. In contrast, TLR7 ligands were ineffective. Purified γδ T cells did not directly respond to TLR8 co-stimulation but required the presence of monocytes. Further experiments revealed a critical role of IL-1β and IL-18, and to a slightly lesser extent of IL-12p70, in the co-stimulation of Vδ2 T cells by TLR8 and TLR7/8 RNA ligands. Results of intracellular cytokine expression were validated by ELISA analysis of cytokines in cell culture supernatants. The cell context-dependent adjuvant activity of TLR8 and TLR7/8 RNA ligands described here might be important for the future optimization of γδ T-cell based cancer immunotherapy.